(untitled) (KYAMC Journal, 2019)
Background: The Carabelli cusps are a tubercle or a additional cusp or a ridge on the palatal surface of the mesiopalatal cusps of maxillary first molars and maxillary seconds deciduous molars. Objectives: The aim of this study was to determine the frequency of cusps of carabelli in permanent first maxillary molars in selected Bangladeshi population. Materials and Methods: This observational study was carried out at MH Samorita Medical College and Dental unit from January 2017 to May 2018 with 104 subjects in young adult individuals. Results: Out of 104 individual the tubercle was present in 55 with a percentage of 52.88%. Among this the total number of male with tubercle 27(49.09%) and female was 28(50.51%). Conclusion: The Carabellis tubercle is mainly used for differentiation between different populations. Frequency of occurrence of Carabelli trait is moderate among Bangladeshi people. KYAMC Journal Vol. 9, No.-4, January 2019, Page 163-165